Joint audit and accuracy of the auditor's report: An empirical study - Julia Baldauf; Rudolf Steckel (International Journal of Economic Sciences and Applied Research, 2012)
This study examines the effects of a joint audit on auditor's report consensus and accuracy. We investigate whether a joint audit, particularly the report issued, improves an audit's quality. We measure the audit's quality using the degree of auditor consensus in the auditor's report. We also use an expected opinion, which we believe is appropriate in the defined circumstances, as a scale for the measurement of the report's accuracy. Participants in the study were statutory auditors from Austria and Germany. At present, manners of improving audit quality and auditing decisions are being intensively discussed in the European Union and everywhere in the world. The joint audit approach is a very current topic in this discussion. Regulators and standard setters are extensively examining the benefits of various audit approaches. Nevertheless, in most countries, the joint audit approach is still utilised on a voluntary basis and is not very common. Our study provides evidence that auditors who use a joint audit approach achieve higher consensus and greater accuracy. In light of current discussion on improving the quality of audits by implementing new methods and regulations, these results are significant for both auditing practice and audit research. Despite this importance, there are very few studies and little research on improving quality through the use of a joint audit approach. Our results demonstrate the need for further investigation of the determinants of audit performance when using a joint audit approach. Using a case study research design and an interview, we draw conclusions and discuss necessary future research.
Keywords: C12; M40; M42; 330; audit quality; auditor's report; consensus; empirical study; joint audit; Wirtschaftsprüfung; Dienstleistungsqualität; Grundsätze ordnungsmäßiger Prüfung